RANCANG BANGUN SISTEM PEMBERIAN MAKAN DAN MINUM PADA ANAK AYAM RAS PETELUR MENGGUNAKAN SENSOR LOADCELL DAN HC-SR04 - Lutvy Dwi Pertiwi; n/a Nurussa’adah; Ali Mustofa (Jurnal Mahasiswa TEUB, 2023)
Management of feeding and drinking is the key to the successful development of laying hens. Food left in the coop will be damp and a source of viruses so that the chicks can contract the disease. Lack of drinking can disrupt the growth of chicks because the amount of drinking determines the amount of food consumed. The feeding system is carried out at the same time every day, namely at 07.00, 15.00 and 21.00. Feeding is also given according to the needs of the chicks based on the age of the chicks. Meals are weighed using a loadcell sensor which is located where the chicken feed container is in the cage. The actuator used in the feeding system is a servo. The drinking system is carried out when the water in the container in the cage runs out. To detect the water level in the container in the cage, the HC-SR04 sensor is used. The actuator used in the drinking system is a DC water pump with a relay as an automatic switch. Water in the cage is provided throughout the day. All systems are controlled using the ESP32 microcontroller. Keywords: Laying Chicks, Feed, Drink, Loadcell, HC-SR04